Reflections and a Vision Toward a Sustainable Education in Electrical Engineering : Next generation of electrical engineers - Godoy Simões, Marcelo; Ribeiro, Paulo F. (IEEE, 2024)
The area of Electrical and Electronics Engineering had been evolving tremendously in the past 100+ years, from electrotechnology of the 20th century then electronics, microprocessors, computers, analog, digital and advanced control, with software becoming further and more advanced, cybernetics, continuous path on intelligence based solutions, the 21st century made the reality of distributed computing, cloud-based services, ultrafast real-time execution of control with digital twin, incorporation of highly sophisticated mathematical models, and then artificial intelligence becoming prominent, further with a Nobel Prize for AI developments for computer scientists. Electrification is also a process of empowering individuals and is bringing change to our modern society. Allowing industry and social impact requires effective renewable generation technologies to supply a network and ever evolving dynamic demand, this critical life-sustaining infrastructure. In this paper the authors describe how the past has shaped our present, and where we are at right now and attempting forecast and advise regarding pathways towards the next generation of Electrical Engineers.
Keywords: Surveys; Education; Electrification; Artificial intelligence; Sustainable development; Next generation networking; Electrical engineering education; Curriculum development; Educational programs; History; Software engineering; Forecasting; fi=Sähkötekniikka|en=Electrical Engineering|